A comparative study of reflex thresholds for puretone narrow-band noise and wideband noise in normal hearing loss - MA, Mythili (Journal of All India Institute of Speech and Hearing)
Middle Ear muscle reflex· is one of the feed back systems in the hearing organ Erik Borg, 1972).